Prevalence and Factors Associated with Depression and Anxiety among HIV-infected Pregnant Women in Kilimanjaro Region, Tanzania - Ngocho, James Samwel (Department of Psychiatry and Mental Health, 2019)
Introduction: Antenatal depression and anxiety in women living with HIV are associated with a number of poor maternal and child outcomes, and undermine the world target of eliminating mother-to-child transmission (MTCT) of HIV. Despite the importance of antenatal mental health, the data on the factors associated with common mental illnesses in HIV-infected women are limited. Thus, the aim of the present study was to determine the prevalence and factors associated with depression and anxiety among pregnant women living with HIV and attending antenatal clinics in Kilimanjaro region, Tanzania. Methods: We analysed the baseline data from an ongoing cohort study of 200 pregnant women living with HIV and attending antenatal care in two districts of the Kilimanjaro region. Women were eligible for inclusion in the parent cohort study if they were HIV-infected and in their second or third trimester of pregnancy. Antenatal depression and anxiety were assessed using the Edinburgh Postnatal Depression Scale and the Brief Symptom Scale, respectively. A multivariate logistic regression model was used to assess the factors that were independently associated with anxiety, depression and comorbidity of anxiety and depression. Variables with a p-value less than 0.15 in univariate analysis were included in the final multivariate model. Results: Participants had a median (IQR) age of 30 years (26-35). About half were married (n=98, 49.0%) and knew their HIV status prior to the index pregnancy (n=105, 52.5%). When asked whether they had disclosed their status to anyone, 159 (79.5%) had disclosed to at least one person and more than half (n=119/170, 70.0%) had disclosed to their sexual partner. Fifty (25.0%) screened positive for possible depression and this was associated with being single (aOR=4.0, 95% CI=1.2–13.7), food insecurity (aOR=2.6, 95% CI=1.0–6.6), and HIV shame (aOR=1.2, 95% CI=1.1–1.3). Of the 197 women who completed the anxiety questionnaire, 47 (23.5%) screened positive for anxiety which was associated with being ashamed of having HIV (aOR=1.1, 95% CI=1.1 – 1.2). The prevalence of comorbid symptoms of depression and anxiety was 17.8% (n=35). HIV shame and lifetime experience of violence (aOR=3.4, 95% CI=1.2 – 9.6) were found to be independently associated with comorbid depression and anxiety. Conclusion: One in every four pregnant women living with HIV screened positive for anxiety and/or depression. The majority of women with depressive symptoms also had anxiety symptoms. In this population, a number of factors were associated with depression and anxiety. These factors ranged from marital status and lifetime experience of violence, food insecurity to HIV-related shame. In order to successfully engage women in HIV care and support their well- being, prevention of MTCT (PMTCT) programmesshould have strategiesto screen and support women with mental illnesses.